Modern Approach to the Principles of Treatment of the Course and Complications of Ovarian Apoplexy in Women with Thrombocytopathy - Lutfulla Saydullayevich , Makhmonov; Mamatkulova Feruza Haydarovna; Amerova Dilafruz Abdikhalimovna; Umarov Zafar Mardonovich (Miasto Przyszłości, 2023)
The occurrence of autoimmune diseases in modern medicine is growing rapidly. In particular, the increasingly damaged and deteriorating ecological environment, the artificialization of food and modern lifestyle - all this leads to the derailment of the immune system, and as a result, the human body does not recognize its own cells and produces antibodies against them. As a result, disorders of some organs and systems, as well as the whole body, occur